Analysis of Multi-Frequency Signal Processing Systems - D. I. Popov (Известия высших учебных заведений России: Радиоэлектроника)
A processing system of multi-frequency signals on the background of correlated (passive) interference is considered. The article presents a comparative analysis of characteristics of multi-processing systems of interperiod processing with various multiplex systems on coherent rejection of interference and subsequent non-coherent accumulation of rejection results. The criteria used in the analysis are high-speed and power characteristics as well as processing system detection characteristics. The analysis of the various options for building of multi-frequency interperiod processing systems with non-coherent accumulation makes it possible to evaluate the advantages and disadvantages of these systems. Frequently practiced algorithm of interference rejection after multiplexing provides the best speed performance, but it gives way to the schemes carrying out interference separate rejection in each frequency channel, which, in turn, can significantly improve signal detection conditions for blind target speeds as compared to single frequency systems.